Recovery of Au(III) ions by Au(III)-imprinted hydrogel - KÖK YETİMOĞLU, ECE; KAHRAMAN, MEMET VEZİR; ÇUBUK, SONER (SPRINGER INTERNATIONAL PUBLISHING AG, 2016)
A new Au(III)-imprinted hydrogel (Au(III)-Imp) was prepared by the photopolymerisation of 4-acryloylmorpholine (AcM), 2-hydroxyethyl acrylate (HEA), and poly(ethylene glycol) diacrylate (cross-linking monomer, PEG-DA) in the presence of gold ions. In addition, non-imprinted hydrogel (N-Imp) was similarly prepared without Au(III) ions The Au(III)-Imp hydrogel was characterised by several techniques. To achieve the optimal conditions, effect of pH, time, and initial metal ion concentrations were investigated using a batch system. The pre-concentration factor for Au(III) ions was found to be at least 100. The analytical parameters of the method were determined and the method was also successfully applied to computer circuit board scrap samples. The reusability of the Au(III)-Imp hydrogel was also determined. (C) 2016 Institute of Chemistry, Slovak Academy of Sciences
Keywords: ion imprinted hydrogel; 4-acryloylmorpholine; gold(III) removal; UV curing; SELECTIVE ADSORPTION; GOLD RECOVERY; ELECTRONIC WASTE; METAL IONS; SAMPLES; GEL; PRECONCENTRATION; EXTRACTION; GOLD(III); POLYMERS